Establishment of complete blood count reference intervals for Chinese preschoolers - Wang, Guo‐Cheng (J Clin Lab Anal, 2016)
BACKGROUND: Reference intervals are critical for interpreting test results of a clinical laboratory. The aim of this study was to establish local reference intervals of complete blood count for healthy preschoolers in China. METHODS: Three thousand eight hundred and twenty‐one blood specimens from children aged 4 months to 6 years were collected and analyzed. Complete blood counts were determined by Sysmex XT‐4000i Automated Hematology Analyzer. The nonparametric 2.5th to 97.5th percentile reference ranges were calculated according to CLSI EP28‐A3c guideline. RESULTS: Reference intervals for each blood cell parameter are determinded as follows: total WBC 4.86‐12.1×10(9)/L for males and 4.73‐12.3×10(9)/L for females; RBC 4.13‐5.32×10(12)/L for males and 4.08‐5.24×10(12)/L for females; HGB 109‐145 g/L for males and 111‐143 g/L for females; HCT 33.1‐41.2% for males and 33.3‐41.1% for females; MCH 23.5‐29.7 pg for males and 24.6‐30.0 pg for females; MCHC 320‐365 g/L for males and 321‐362 g/L for females; MCV 71.4‐85.1 fL for males and 73.8‐86.9 fL for females; RDW‐SD 33.5‐41.9 fL for males and 33.5‐41.0 fL for females; RDW‐CV 12.0‐15.2% for males and 11.8‐14.5% for females; PLT 181‐475×10(9)/L for males and 179‐456×10(9)/L for females; PCT 0.18‐0.44% for males and 0.18‐0.43% for females; MPV 8.20‐11.6 fL for males and 8.20‐11.5 fL for females; PDW 8.40‐14.4 fL for males and 8.40‐14.0 fL for females; P‐LCR 12.0‐36.6% for males and 11.8‐35.6% for females. CONCLUSIONS: We established local complete blood count reference intervals for apparent healthy preschoolers in China. It is necessary to establishing region‐specific reference intervals of complete blood count for preschoolers.